Original Blue Light-Emitting Diphenyl Sulfone Derivatives as Potential TADF Emitters for OLEDs - Zommere, Margarita Anna; Tetervenoka, Natalija; Pidluzhna, Anna; Grzibovskis, Raitis; Blazevicius, Dovydas; Krucaite, Gintare; Tavgeniene, Daiva; Grigalevicius, Saulius; Vembris, Aivars (MDPI, 2024)
Organic light-emitting diodes (OLEDs) have emerged as one of the dominant technologies in displays due to their high emission efficiency and low power consumption. However, the development of blue color emitters has fallen behind that of red and green emitters, posing challenges in achieving optimal efficiency, stability, and accessibility. In this context, thermally activated delayed fluorescence (TADF) emitters hold promise as a potential solution for cost-effective, exceptionally efficient, and stable blue OLEDs due to their potential high efficiency and stability. TADF is a principle where certain organic materials can efficiently convert both singlet and triplet excitons, theoretically achieving up to 100% internal quantum efficiency. This research focused on diphenyl sulfone derivatives with carbazole groups as TADF compounds. Quantum chemical calculations and photoluminescence properties show the potential TADF properties of the molecules. New materials exhibit glass transition temperatures that would classify them as molecular glasses. Depending on the structure of the molecule, the photoluminescence emission is in the blue or green spectral region. Organic light-emitting diodes were fabricated from neat thin films of emitters by the wet casting method. The best performance in the deep blue emission region was achieved by a device with a turn-on voltage of 4 V and a maximum brightness of 178 cd/m2. In the blue-green emission region, the best performance was observed by an OLED with a turn-on voltage of 3.5 V, reaching a maximum brightness of 660 cd/m2. © 2024 by the authors. --//-- This is an open-access article Zommere, M.A.; Tetervenoka, N.; Pidluzhna, A.; Grzibovskis, R.; Blazevicius, D.; Krucaite, G.; Tavgeniene, D.; Grigalevicius, S.; Vembris, A. Original Blue Light-Emitting Diphenyl Sulfone Derivatives as Potential TADF Emitters for OLEDs. Coatings 2024, 14, 1294. https://doi.org/10.3390/coatings14101294 published under the CC BY 4.0 licence.
This work was supported by the Research Council of Lithuania (Grant No. S-LLT-19-2). This work was supported by VIAA project No. 1.1.1.2/VIAA/4/20/592. This work was supported by the M-era Net 2019 call project "Enabling a Commercially Viable Long Lifespan and High Efficiency Omni Friendly OLED Lighting Source with G2 and G3 Emitters". Institute of Solid-State Physics, University of Latvia, received funding from the European Union's Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; blue emitters; diphenyl sulfone derivatives; organic light-emitting diodes; thermally activated delayed fluorescence